ENHANCING ENVIRONMENTAL LITERACY THROUGH THE IMPLEMENTATION OF EXPERIENTIAL AND JOYFUL LEARNING MARINE EDUTOURISM WITHIN THE BAROS MANGROVE ECOSYSTEM OF BANTUL - Hayati, Riza Sativani; Ma'rifah, Destri Ratna (As-Sidanah : Jurnal Pengabdian Masyarakat, 2026)
Low environmental literacy among Indonesian students, necessitates innovative pedagogical models such as Experiential and Joyful Learning Marine Edutourism (EJoy-ME). This study evaluates the effectiveness of the EJoy-ME model, based on the local potential of the Baros Mangrove, in enhancing students' environmental literacy. A quasi-experimental pretest-posttest design was implemented in December 2026 with 42 junior high school students from SMP IT Ar Rahmah and SMP Muhammadiyah Kretek. The results show that average literacy scores increased from 46.55 to 52.33 (N-Gain = 0.11, Low category). However, significant improvements were achieved in the issue-analysis domain, where students' ability to identify environmental problems rose from 21% to 74% (N-Gain = 0.67, Moderate category) and formulating solutions increased from 31% to 74% (N-Gain = 0.62, Moderate category). Achievement of the Minimum Completeness Criteria (KKM) also improved from 19% to 36%. These findings indicate that the 6-stage EJoy-ME syntax effectively bridges the gap between theoretical knowledge and pro-environmental action by fostering deep emotional and cognitive engagement within local ecosystem.